Quantification of amygdalin, prunasin, total cyanide and free cyanide in powdered loquat seeds. Issue 9 (1st September 2020) - Tanaka, Tomoya; Kimura, Keisuke; Kan, Kimiko; Katori, Yoshiko; Michishita, Kumi; Nakano, Hisako; Sasamoto, Takeo
ABSTRACT: Amygdalin, prunasin, total cyanide and free cyanide concentrations in 12 powdered loquat seeds were investigated. Loquat ( Eriobotrya japonica ) is a species of flowering plant in the family Rosaceae, and its fruit is quite popular in Japan. Amygdalin and prunasin were measured using LC–MS/MS. Total cyanide was measured by enzymatic treatment, steam distillation and colorimetric quantification using the pyridine–pyrazolone method. Free cyanide was measured without enzymatic treatment. The mean concentrations of amygdalin, prunasin, total cyanide and free cyanide in powdered loquat seeds were 5900, 760, 410 and 44 mg/kg, respectively. The range of each quantitative value was extensive. Seven out of twelve samples were at risk for exceeding the acute reference dose (ARfD) of cyanide.